Combating financial crimes through forensic accounting in Nigerian public sector - Olaoye, A. (Journal of Economic Research & Business Administration, 2020)
Financial crimes are a global issue which remains unresolved. These crimes have plagued every corner of the world economy. The adverse effect of these crimes is immense in Nigeria. Continuous research confirmed a strong demand for the forensic accounting of preventing, detecting and arresting of financial crimes menace in Nigeria and the rest of the world. However, the studies of combating financial crimes through forensic accounting are very few in literature and not fully explored in Nigerian public sector. This study therefore, sets to examine the impact of forensic accounting techniques for combating financial crimes in Nigerian public sector. This study employs a survey research design and purposive sampling technique to select the sample of eighty six (86) accountants and auditors of the three selected ministries in Osun State, Nigeria. Both primary and secondary data were collected. The primary data was collected through a designed structured questionnaire. The data collected was analyzed using descriptive and inferential statistical tools. It was found that combating of financial crimes in Nigerian public sector through the application of forensic accounting is possible as the p– value = 0.00 < 0.01. This study therefore concluded that, government of Nigeria should increase the interest in and facilitate the growth of forensic accounting by giving legal backing for proper monitory and investigation of alleged cases of financial crimes. This study recommended that, all government ministries, agencies and parastatals should establish forensic accounting unit to help strengthen internal controls and ensure thorough investigation in order to prevent, deter and detect financial crimes and the University regulatory body as well as the accounting professional bodies should ensure that forensic accounting courses are included in the curricula to ensure the training and increased awareness of forensic accounting in Nigeria.